Updates on the Status of Vitamin D as a Risk Factor for Respiratory Distress Syndrome - Vesara Ardhe Gatera; Rizky Abdulah; Ida Musfiroh; Raden Tina Dewi Judistiani; Budi Setiabudiawan (Hindawi Limited, 2018)
To update the guidelines regarding vitamin D status in respiratory distress syndrome, we reviewed recent human and animal studies on the benefits of vitamin D in respiratory distress. We searched PubMed and ProQuest for studies on the use of vitamin D from 2009 to 2017. The common parameters in these studies included the use of lung tissue, phospholipids, blood, and plasma to assess the effects of vitamin D on respiratory syndrome. The metabolized form of vitamin D used in these studies was 1,25(OH)2D3 in animal studies and 25(OH)D in human studies. Vitamin D supplementation decreases the risk of respiratory distress syndrome, improves the quality of life, and is relatively effective and safe for preterm neonates as well as during lung maturation. However, although vitamin D supplementation may offer benefits for respiratory distress syndrome, the optimal dosing strategies for specific types of risk factors in the lungs must be clarified to confirm the therapeutic efficacy.